ENT 530 Socia Media Portfolio / Siti Amirah Amiruddin - Amiruddin, Siti Amirah (2019)
My business was registered with Syarikat Suruhanjaya Malaysia through ezBiz system under my personal name, Siti Amirah Binti Amiruddin and started it commencement on 29th September 2019. This business is sole proprietorship business. The business is namely CHEELICIOUS CRUCHIES and also creating their own vision and mission to be accomplished. The product that Cheelicious Crunchies sell are snack which is POPIA CHEESE. Customer can make order through Facebook page (Cheelicious Crunchies) or WhatsApp application. We are selling our products with an affordable price. I promoted my product mainly through Facebook Page with tease, hard sell and soft sell. Those are for my marketing techniques. For hard sell post, I use AIDA selling concept to attract people buying my product. For soft sell, I have posted it with title, introduction, content and call to action concept. Within two months starting from October to November, I managed to accumulate sales of RM71 and reported the sales report through eUsahawan system.